Application of Refuse-Derived Fuel (RDF) Plant in Piyungan Landfill Municipal Solid Waste Management - Diananto Prihandoko; Chandra Wahyu Purnomo; Primanda Kiky Widyaputra; Nasirudin Nasirudin (ASEAN Journal of Chemical Engineering, 2022)
Piyungan Landfill is the biggest landfill in the Yogyakarta Province that still operates in overcapacity condition. A new alternative is highly required in solid waste management in the landfill, which can reduce the volume of the waste coming into it and decrease the need for a new landfill area. Refused-derived fuel (RDF) plant is one of the technological alternatives in solid waste management that has the potential to reduce the volume of solid waste and change the waste into fuel. The study analyzed the potential of the application of the RDF to reduce the volume of solid waste in the Piyungan landfill and its economic feasibility. The results of the analysis showed that during the operational period of the RDF plant, the volume of the solid waste coming into the landfill could be annually reduced by 43% on average. The results of the economic analysis show that the RDF plant in the Piyungan Landfill is feasible to apply with an NPV of IDR 281.46 billion, an IRR of 24%, and a payback period of 6 years.